Stoning the keepers at the gate: society's relationship with law enforcement - Blum, Lawrence N. (Lantern Books, 2002)
What the public doesn't see -- Attitudes toward law enforcement in American society -- Changing attitudes, changing times -- The making of police officers -- Shaping the new police recruit -- Police agencies -- Ethics